How to supply more solar energy to reactive sites for highly efficient artificial photosynthesis - Yasuhiko Takeda; Takeshi Morikawa (JPhys Energy)
Artificial photosynthesis mimics the function of natural photosynthesis, producing solar fuels from only CO _2 and water using solar energy. Hence, it is a promising technology to reduce net CO _2 emission. The first step of the artificial photosynthetic production is harvesting solar energy to supply energetic charge carriers, which is common to solar cells (SCs) used for solar photovoltaics. In this Review, we discuss the means to improve the efficiencies of the first step. The steadiest means is to split solar spectrum into plural ranges using plural light-absorbing materials with different bandgaps. Indeed, this means has been successfully applied to solar photovoltaics to realize highly efficient multijunction SCs. We review concrete implementations of the solar-spectrum splitting on the three types of the artificial photosynthetic devices: the combination of SCs and electrochemical reactors, photoelectrochemical reactors using photoelectrodes, and photocatalytic reactors. In particular, we highlight the similarities and differences in the design criteria between the artificial photosynthetic devices and SCs used for solar photovoltaics; the differences originate from that the former operates at a specific narrow voltage (or carrier energy) range slightly higher than the thermodynamic threshold of the target reaction whereas the latter at the maximal power (product of voltage and current) point. Application of new concepts originally developed for solar photovoltaics including photon upconversion, two-step excitation via intermediate bands, and hot-carrier extraction would be attractive, in particular for the photocatalysts to balance the high efficiency and simple configuration. Some of these concepts on the photocatalysts have been proven, however, not yet improved the performance. Thus, this Review serves as a guide for the strategies to supply more solar energy to the reactive sites. Technological developments based on these strategies could accelerate the practical and widespread use of artificial photosynthesis, contributing to solving the global warming problem.